2009
DOI: 10.1007/s11814-009-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CeO2-addition sequence on the performance of CeO2-modified Ni/Al2O3 catalyst in autothermal reforming of iso-octane

Abstract: Two types of CeO 2 -modified Ni/Al 2 O 3 catalysts were prepared by a consecutive impregnation method with different sequences in the impregnation of Ni and CeO 2 , and their performance in autothermal reforming (ATR) of isooctane was investigated. Catalysts prepared by adding CeO 2 prior to the addition of Ni, Ni/CeO 2 -Al 2 O 3 , produced larger amounts of hydrogen than those obtained using catalysts prepared by adding the two components in an opposite sequence, Ni-CeO 2 /Al 2 O 3 . The results of H 2 chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Autothermal reforming (ATR) of CH 4 is a combination of steam reforming (SR) and partial oxidation (PO) of CH 4 [1][2][3][4][5][6][7][8]. SR is a highly endothermic reaction that requires an external heat source.…”
Section: Introductionmentioning
confidence: 99%
“…Autothermal reforming (ATR) of CH 4 is a combination of steam reforming (SR) and partial oxidation (PO) of CH 4 [1][2][3][4][5][6][7][8]. SR is a highly endothermic reaction that requires an external heat source.…”
Section: Introductionmentioning
confidence: 99%
“…When Ni species are loaded onto the appropriate support, the positive metal/support synergistic effect will remarkably improve their catalytic performance and stability. For example, Choi et al demonstrated that the addition of CeO 2 to Al 2 O 3 prior to loading Ni species increased the dispersion of the Ni species on the support due to improved CeO 2 -Ni interaction, leading to increased hydrogen yield and longer lifetime of the catalyst during auto-thermal reforming of iso-octane [20]. Sánchez-Sánchez et al showed that the existence of Ni-Ce species Ni/CeO 2 -Al 2 O 3 could enhance adsorption and dissociation of water molecules, thus improving their catalytic activity for ethanol reforming [21].…”
Section: Introductionmentioning
confidence: 99%
“…Ni/Al 2 O 3 presents a cheap catalytic system which is relatively stable and possesses favorable metal–support interactions . Hence a number of ways of improving the catalytic activity, stability, and applicability of nickel-based catalysts for low-temperature gasification have been investigated and reported in the literature. The role of Ni/Al 2 O 3 catalysts in C–C and C–O bond cleavage during biomass and tar conversion is reported in the literature. , The acidic alumina support provides a high surface area, good thermal stability, high adsorption capacity, and excellent mechanical strength, for the active nickel species, with minimal agglomeration, sintering, or crystal growth especially when the nickel loading is not more than 20 wt %. It was reported that the incorporation of an appropriate promoter could enhance the catalytic properties and give rise to a new set of kinetic parameters for the same reactive system. ,, Choi et al reported that ceria in Ni/CeO 2 /Al 2 O 3 catalyst assisted in improving the hydrogen yield, attenuating coke deposition during autothermal reforming of isooctane . Furthermore, the reactor type is very vital in ensuring that a reasonable biomass or tar conversion is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…9−11 It was reported that the incorporation of an appropriate promoter could enhance the catalytic properties and give rise to a new set of kinetic parameters for the same reactive system. 2,11, 12 Choi et al reported that ceria in Ni/ CeO 2 /Al 2 O 3 catalyst assisted in improving the hydrogen yield, attenuating coke deposition during autothermal reforming of isooctane. 12 Furthermore, the reactor type is very vital in ensuring that a reasonable biomass or tar conversion is achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation